MODEL PEMBELAJARAN BAHASA ARAB YANG TERFOKUS PADA SISWA (STUDENT-CENTERED LEARNING/SCL) - Ahmad Asse (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2018)
This paper would like to descripte the characteristics of learning that focused on the learners, the benefits, the weaknesses and the steps of its use to achieve the goal of learning Arabic. Learning model is an important part which is understood by every Arabic teacher to be able to present the condition of learning that is always fun for learners. An effective model for learning in Arabic is the learning model that concentrated to student. The use of this learning model is believed to be able to improve the four competencies of Arabic learners, namely the ability to speak, write, read and hear. For this reason, an Arabic teacher must understand the various variants of an effective learning model which centered on the learning potential of students in order to present the materials in an enjoyable. Therefore, it is important for any Arabic teacher to change the teacher-centered paradigm which is conventional teaching towards a modern learning paradigm which centered to the creative ability of students during the Arab learning proccess. The use of learning models which focused to learners in Arabic learning should be supported by teacher innovation that can empower learners to be active during learning. In addition, the teacher seeks to construct the latest Arabic material by utilizing the technology media relevant to the progress of the global education world, especially in learning Arabic as the language of the Islamic world and religious language.